2016
DOI: 10.1136/bcr-2015-212871
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular parenchymal extension of the ablation zone following liver microwave ablation

Abstract: A 69-year-old man who presented with abdominal discomfort was, on examination, found to have a palpable abdominal mass. Contrast-enhanced CT showed a mass arising from the inferior vena cava, which biopsy confirmed to be a leiomyosarcoma. One month after chemoradiotherapy, CT demonstrated a new 15 mm solitary central right liver metastasis. Microwave ablation (MWA) of the metastasis was performed using an Acculis Sulis V system (Angiodynamics, USA) at a power of 140 Watts for 4 min, with no immediate complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Thrombosis of intrahepatic vessels has been reported in the literature and is a recognised complication [9]. However extension of the ablation zone along vessels has only been reported once in a patient where there was evidence of ablation zone extension around a thrombosed hepatic vein branch [10]. Perivascular extension of the ablation zone has been reported as an incidental finding in two in vivo animal studies of liver MWA [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thrombosis of intrahepatic vessels has been reported in the literature and is a recognised complication [9]. However extension of the ablation zone along vessels has only been reported once in a patient where there was evidence of ablation zone extension around a thrombosed hepatic vein branch [10]. Perivascular extension of the ablation zone has been reported as an incidental finding in two in vivo animal studies of liver MWA [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A more recent in vivo study demonstrated vessel damage away from the ablation zone but did not mention extension of the ablation zone in the perivascular parenchyma [13]. This effect is important because thermal injury to vessels may precipitate thrombosis, as seen in the only reported clinical case and in vivo studies [10][11][12][13]. Vascular thrombosis is not rare following MWA [9], and in some cases can be a serious complication [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…One way to obtain this is information is to apply IRE to perfused human organs (both cancer-containing and healthy). Our previous work on the clinical application of microwave ablation (MWA) to solid tumours demonstrated that a perfused organ could provide different findings, and hence a different treatment algorithm, to that derived from non-viable and non-perfused tissues [ 104 , 105 , 106 ]. Applying IRE to perfused human pancreas ex vivo, using organs deemed unsuitable for transplant and therefore declined for clinical use may aid the development of an alternative treatment protocol and help define protective criteria for vital structures.…”
Section: Pathological Response To Pancreas Ire Therapy and Mechanism Of Actionmentioning
confidence: 99%